Plasma BDNF and TrkB mRNA in PBMCs Are Correlated With Anti-depressive Effects of 12-Weeks Supervised Exercise During Protracted Methamphetamine Abstinence - Yang, Jue; Tan, Jun; Zheng, Lan; Lu, Chun Xia; Hou, Wen Qi; Liu, Yi; Li, Qiu Fang; Li, Jin Xiu; Cheng, Dan; Luo, Xu; Zhang, Jun (Frontiers in Molecular Neuroscience, 2020)
Purpose: The aim of this study was to evaluate the potential neurotrophic factors and expression of neurotrophin receptors in peripheral blood mononuclear cells linked with the antidepressant action of exercise intervention during protracted methamphetamine abstinence. Materials and Methods: A total of 72 male methamphetamine addicts, including 47 individuals with depression and 25 individuals without depression were recruited in this study. Individuals with depression were divided into depression control group and depression exercised group. Consequently, twelve weeks supervised exercise intervention was applied. Depression and anxiety were analyzed; plasma BDNF, NGF, NT-3, NT-4 and proBDNF levels were tested using enzyme-linked immunosorbent assay; the mRNA expressions of TrkA, TrkB-FL, TrkB-T1, TrkCB, P75NTR in peripheral blood mononuclear cells were detected by quantitative real-time PCR. Results: NT-4 Plasma levels were correlated with depression (r = -0.330, p = 0.005), which remained significant after Bonferroni correction. In addition, the BDNF and NT-3 levels in the plasma were significantly correlated with depression (r = -0.268, p = 0.023; r = -0.259, p = 0.028), but did not reach significance after Bonferroni correction. The BDNF, NT-3, and NT-4 plasma levels were significantly different between the depressive control group and depressive exercise group using pre-exercise values as the covariate. The fold changes in TrkB-FL and TrkB-T1 mRNA in peripheral blood mononuclear cells between the post-exercise and pre-exercise demonstrated a remarkable decrease (fold change = -11.056 and -39.055). Conclusions: Exercise intervention can alleviate depression and anxiety during protracted methamphetamine abstinence. Decrease in BDNF and the expression of TrkB in peripheral blood mononuclear cells occur following the exercise intervention.